New dinuclear hydrido-carbonyl rhenium complexes designed as photosensitizers in dye-sensitized solar cells. (3rd February 2016) - Veronese, Lorenzo; Procopio, Elsa Quartapelle; De Rossi, Francesca; Brown, Thomas M.; Mercandelli, Pierluigi; Mussini, Patrizia; D'Alfonso, Giuseppe; Panigati, Monica
Abstract : Dye-sensitized solar cells based on dinuclear hydrido-carbonyl rhenium complexes have been developed, achieving an overall solar conversion efficiency of 1.0%. Abstract : The possible use of some dinuclear rhenium complexes as sensitizers for dye sensitized solar cells (DSSCs) has been investigated. They have general formula [Re2 (μ-X)(μ-Y)(CO)6 (μ-pyridazine-4-COOH)], with X = Y = Cl (1 ), X = H, Y = benzoato (2 ), and X = H, Y = 4-diphenylaminobenzoato (3 ). An original synthetic strategy has been set for preparing the hydrido-carboxylato derivatives2 and3 . They have been indicated by DFT and TD-DFT computations as the most promising dyes, endowed with good light harvesting capability. The complexes have absorption maxima in the range of 405–443 nm, on TiO2 films, arising from metal-to-ligand-charge transfer transitions. Cyclic voltammetry experiments have been performed on the derivatives containing the methyl ester of the pyridazine-4-COOH acid, showing electrochemical band gaps in the range of 2.25–1.63 eV. The best DSSC results have been obtained using complex3, with an overall solar-to-electric conversion efficiency of 1.0%. Noteworthy the presence of a hydrido ligand did not show any detrimental effect on the stability of the sensitizers under the operating conditions.